Do the Various Indirect Bonding Techniques Provide the Same Accuracy for Orthodontic Bracket Placement? (Randomized Clinical Trial) - Ammar Sh. Al-Ubaydi; Dheaa Al-Groosh (International Journal of Dentistry, 2024)
Background. For orthodontic treatment to be effective, bracket placement must be precise to make the finishing stage easier, leading to an ideal occlusion with minimal intervention. This study aimed to evaluate the accuracy of manual and digital bracket positioning techniques utilizing computer-aided design and computer-aided manufacturing (CAD/CAM) jigs, 3D-printed indirect bonding trays (IBT), and double-layer vacuum-formed thermoplastic IBT. Methods.This study was done by scanning the dental arch of 30 orthodontic patients. The virtual setup and bracket positioning were performed with the Insignia™ system for ten patients, and 3D Maestro® software was used for the virtual setup of the remaining 20 patients. At the same time, the bracket positioning of 10 patients was done digitally by the 3D Maestro® software and the remaining 10 patients manually through the Ray Set® device. IBT were fabricated by CAD/CAM system, 3D printer, and vacuum-formed thermoplastic machine. A virtual bracket position was compared to the actual bracket position using the best-fit method of 3D digital superimposition in Geomagic® Control X™ (CX) software to determine how accurate it was in terms of linear and angular accuracy. Statistical analyses using SPSS 26.0 including Bland–Altman plots were used to assess the intra-examiner reproducibility. Shapiro–Wilk test was used to measure normality distribution. Wilcoxon matched-pairs signed rank test was used to analyze the differences between bracket positions within each group. Results. Although there were obvious positional discrepancies between several readings, they were still within clinically acceptable ranges. Conclusions. All types of IBT would translate the planned position of the bracket from the digital and manual techniques to the teeth of patients with accepted precision in both linear and angular measurements; in addition, the error rate is about the same for all types of IBT. This trial is registered with NCT05549089.